339 SURGICAL INPATIENT DELIRIUM: AN AUDIT OF THE DOCUMENTATION OF THE 4AT SCORE. (25th October 2022) - Smyth, H; Mohammed, T; Healy, N; Vallely, S; Byrne, C; Kyne, L; Scanaill, PÓ
Abstract: Background: Postoperative delirium and perioperative neurocognitive disorder are the commonest postoperative complications in patients over 65 years old. This has implications for brain health with an increased risk of length of stay, a higher incidence of morbidity and mortality. Internationally, perioperative teams often fail to routinely screen for delirium. Our aim was to audit the documentation of the 4AT score for surgical inpatients over 65 years old and gain insight into the incidence on surgical wards. Methods: Using the guideline for Perioperative Care for People Living with Frailty undergoing Elective and Emergency Surgery from the CPOC and BGS as a standard, an audit of surgical inpatients over 65 was carried out on 3 surgical wards over 5 days. Data was collected including 4AT documentation on admission, day 1 and day 3 post operatively, type of surgery & anaesthesia and risk factors for delirium (dementia, polypharmacy, opioids & benzodiazepine use, PD, surgery>2h, stroke, alcohol, >2 medical conditions, multiple ward moves). Results: 36 surgical patients over 65 years of age were included in the audit. The average age was 78 years old (range 65-91). 50% were admitted under the orthopaedic team, 31% under general surgical teams, 11% urology and 8% under other surgical specialties. 33% of patients had a 4AT documented at any stage during their admission and 25% of patients had a baseline 4AT documented preoperatively. The incidence of delirium was 18.7%. Surgical risk factors for delirium were found in 69% of older inpatients. Conclusion: Delirium screening was underused in our cohort of older surgical patients despite a proportion of patients developing delirium postoperatively. Under recognition of delirium perioperatively is associated with poor outcomes and higher morbidity and mortality. Further interdisciplinary educational sessions are required to increase awareness and screening of delirium in surgical patients >65 years old with the aim to re-audit in 6 months.